Tingkat kemiskinan dan keterbatasan pada sumber daya akibat urbanisasi di DKI Jakarta - Riandani, Kania Putri; Adila, Muhammad Faras; Zid, Muhammad; Saputro, Hikari Dwi; Yusuf, Muhammad (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
Urbanization in DKI Jakarta in 2024 reflects complex socio-economic dynamics that significantly affect urban poverty and resource limitations. This study aims to examine the relationship between urbanization, migration flows, and poverty levels in DKI Jakarta. The research employs a literature review method by analyzing secondary data from the Central Bureau of Statistics (BPS), particularly the 2024 Susenas Migrant Profile, as well as relevant national and international scientific journals published within the last ten years. The findings indicate that the high inflow of migrants, especially lifetime migrants, has increased population density and intensified pressure on urban resources, including adequate housing, clean water, and formal employment opportunities. Inequality in access to resources and economic opportunities has contributed to urban poverty, which reached 4.14 percent in 2024. These findings are consistent with Alex Inkeles’ modernization theory and Everett S. Lee’s push–pull theory, which suggest that urbanization without inclusive governance and equitable resource management tends to exacerbate social inequality. Therefore, inclusive and sustainable urban development policies are essential to mitigate the negative impacts of urbanization on poverty in DKI Jakarta.